DECONSTRUCTING PORTRAYALS OF WOMEN IN PAKISTANI TELEVISION: A CRITICAL DISCOURSE ANALYSIS OF GENDER STEREOTYPES - Lubna Aram Azam; Faria Shaheen; Muskan Iqbal; Dr. Mudasar Jahan (International Journal of Contemporary Issues in Social Sciences, 2024)
Investigating how women are portrayed in Pakistani dramas is the goal of the study. The analysis’s primary goal is to clarify how the drama upholds and encourages gender hierarchies and patriarchy in the program. According to the research, Sar-e-Rah depicts patriarchal gender roles in which women are limited to becoming wives, mothers, or housewives, and men are shown as dominating individuals who utilize language to restrict women’s movement. The research also shows that people are penalized by society for defying the roles that are assigned to them in conventional gender norms, which makes it plausible in the real world. Despite this, the drama contains certain elements that reinforce gender stereotypes by exposing the archetypes of strong women and sensitive males simultaneously.